Data for "Characterization of the performance of a RIT-10and rf-neutralizer for an ABEP system" - Zorn, Jana; Justus Liebig University Giessen (My University, 2025)
Supporting data for the manuscript "Characterization of the performance of a RIT-10and rf-neutralizer for an ABEP system" for the collection "Novel Molecular Propellants for Electric Propulsion" of the Journal of Electric Propulsion. The individual files from Langmuir, OES, RPA, Raman, Mass spectroscopy and Faraday cup measurements are available in the corresponding folders. Most of the file name are self-explanatory, in some cases additional information is given. The files are mostly .txt-files, some .csv-files and one .docx-file. Only the OES data have a .asc data type.
Keywords: ABEP; RIT-10; rf-neutralizer; ddc:530